Effects of Sustained Administration of Quetiapine Alone and in Combination with a Serotonin Reuptake Inhibitor on Norepinephrine and Serotonin Transmission - Chernoloz, Olga (Nature Publishing Group, 2012)
Quetiapine is now used in the treatment of unipolar and bipolar disorders, both alone and in combination with other medications. In the current study, the sustained administration of quetiapine and N-Desalkyl quetiapine (NQuet) in rats in a 3 : 1 mixture (hQuetiapine (hQuet)) was used to mimic quetiapine exposure in patients because rats do not produce the latter important metabolite of quetiapine. Sustained administration of hQuet for 2 and 14 days, respectively, significantly enhanced the firing rate of norepinephrine (NE) neurons by blocking the cell body α(2)-adrenergic autoreceptors on NE neurons, whether it was given alone or with a serotonin (5-HT) reuptake inhibitor. The 14-day regimen of hQuet enhanced the tonic activation of postsynaptic α(2)- but not α(1)-adrenergic receptors in the hippocampus. This increase in NE transmission was attributable to increased firing of NE neurons, the inhibition of NE reuptake by NQuet, and the attenuated function of terminal α(2)-adrenergic receptors on NE terminals. Sustained administration of hQuet for 2 and 14 days, respectively, significantly inhibited the firing rate of 5-HT, whether it was given alone or with a 5-HT reuptake inhibitor, because of the blockade of excitatory α(1)-adrenergic receptors on 5-HT neurons. Nevertheless, the 14-day regimen of hQuet enhanced the tonic activation of postsynaptic 5-HT(1A) receptors in the hippocampus. This increase in 5-HT transmission was attributable to the attenuated inhibitory function of the α(2)-adrenergic receptors on 5-HT terminals and possibly to direct 5-HT(1A) receptor agonism by NQuet. The enhancement of NE and 5-HT transmission by hQuet may contribute to its antidepressant action in mood disorders.